Influence Factors of Social Media and Gadget Addiction of Adolescent in Indonesia - M. Octaviano Pratama; Dwi Harinitha; Susmini Indriani; Bryan Denov; Dimitri Mahayana (Jurnal Sistem Informasi, 2020)
Social media user in Indonesia has growth rapidly since its emergence. In 2019, one of largest social media platform, Facebook has 3 billion users world wide user and 130 million users of them come from Indonesia. Moreover, the other social media like Instagram also has significantly growth with most of user are teenagers. Massive social media usage was caused by more than 100 million active users that use gadget or smartphone to open application like social media. Both of widely social media and gadget usage is not only have possitive impact but also negative impact like mental and behaviour problem if the user has been addicted. Hence the requirement of knowing influence factors of social media and gadget addiction in Indonesia is required in order to prevent addiction of social media and gadget. In this paper, the influence factors of social media and gadget addiction in Indonesia is investigated using several techniques like data science, partial least square, and structural equation modelling